2020
DOI: 10.1038/s41467-020-19477-3
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory function of the AAA4 ATPase domain of cytoplasmic dynein

Abstract: Cytoplasmic dynein is the primary motor for microtubule minus-end-directed transport and is indispensable to eukaryotic cells. Although each motor domain of dynein contains three active AAA+ ATPases (AAA1, 3, and 4), only the functions of AAA1 and 3 are known. Here, we use single-molecule fluorescence and optical tweezers studies to elucidate the role of AAA4 in dynein’s mechanochemical cycle. We demonstrate that AAA4 controls the priming stroke of the motion-generating linker, which connects the dimerizing ta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 76 publications
2
5
0
Order By: Relevance
“…In this control strain, the gpdA-∆C-hookA-S allele was present to ensure that dynein mainly moves towards the microtubule minus end. We found that wild-type dynein moved robustly in the motility assay, and the full-length wB-AAA3 dynein also moves processively along the microtubule (when 3mM ATP instead of 1mM ATP was used), albeit with a very low speed (Figure S4A, S4B and S4C), consistent with previous in vitro data obtained from the yeast dynein motor domain (Cho et al, 2008;Bhabha et al, 2014;DeWitt et al, 2015;Nicholas et al, 2015;DeSantis et al, 2017;X. Liu et al, 2020).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…In this control strain, the gpdA-∆C-hookA-S allele was present to ensure that dynein mainly moves towards the microtubule minus end. We found that wild-type dynein moved robustly in the motility assay, and the full-length wB-AAA3 dynein also moves processively along the microtubule (when 3mM ATP instead of 1mM ATP was used), albeit with a very low speed (Figure S4A, S4B and S4C), consistent with previous in vitro data obtained from the yeast dynein motor domain (Cho et al, 2008;Bhabha et al, 2014;DeWitt et al, 2015;Nicholas et al, 2015;DeSantis et al, 2017;X. Liu et al, 2020).…”
Section: Resultssupporting
confidence: 90%
“…Despite the differences in the mechanisms of plus-end dynein localization, the dynein motor mechanism is most likely conserved in different organisms. Consistent with previous results on the yeast wB-AAA3 dynein motor domain (Cho et al, 2008;Bhabha et al, 2014;DeWitt et al, 2015;Nicholas et al, 2015;DeSantis et al, 2017;X. Liu et al, 2020), the wB-AAA3 mutation also significantly inhibits the in vitro motility of full-length dynein in A. nidulans extract (Figure S4).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, the ATP hydrolysis activity of this site may be greatly reduced. Recent work has shown that blocking ATP binding to AAA4 fully inhibits dynein, whereas blocking ATP hydrolysis has little effect on motor velocity (100). These results indicate that AAA4 remains mostly in the ATP-bound state and that the nucleotide plays a structural role for the AAA1 site to drive the priming stroke of the linker and sliding of the stalk coiled-coils (100).…”
Section: + -mentioning
confidence: 99%